BASIC KNOWLEDGE AND ATTITUDES OF ESP STUDENTS TO WORLD ENGLISHES - Muhalim Muhalim (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2016)
The English for Specific Purposes (ESP) enterprise is protean and comprises three realms of language, pedagogy and content studies. Since it not only focuses on content-based, the responsive nature of ESP should also spotlight the development of language as well as pedagogy. World Englishes (WEs) as consistent growth in ELT practice, has confirmed its position due to the shifting paradigm of teaching ‘only’ native standard Englishes. This paper starts with outlining why WEs should be introduced in ESP classrooms. Later, the paper reports research findings on the students’ knowledge of WEs based on the proposals of Kirkpatrick and Kachru. It also explores the ESP students’ attitudes toward WEs. The ESP students’ basic knowledge and some future constructs to instill WEs concept for ESP students will conclude this preliminary study.Keywords: basic knowledge, attitudes, ESP, World Englishes (WEs)